A minimum dataset for a Level 1 echocardiogram: a guideline protocol from the British Society of Echocardiography. Issue 2 (June 2020) - Hindocha, Rakhee; Garry, David; Short, Nadia; Ingram, Tom E; Steeds, Richard P; Colebourn, Claire L; Pearce, Keith; Sharma, Vishal
Abstract : The British Society of Echocardiography has previously outlined a minimum dataset for a standard transthoracic echocardiogram, and this remains the basis on which an echocardiographic study should be performed. The importance of ultrasound in excluding critical conditions that may require urgent treatment is well known. Several point-of-care echo protocols have been developed for use by non-echocardiography specialists. However, these protocols are often only used in specific circumstances and are usually limited to 2D echocardiography. Furthermore, although the uptake in training for these protocols has been reasonable, there is little in the way of structured support available from accredited sonographers in the ongoing training and re-accreditation of those undertaking these point-of-care scans. In addition, it is well recognised that the provision of echocardiography on a 24/7 basis is extremely challenging, particularly outside of tertiary cardiac centres. Consequently, following discussions with NHS England, the British Society of Echocardiography has developed the Level 1 echocardiogram in order to support the rapid identification of critical cardiac pathology that may require emergency treatment. It is intended that these scans will be performed by non-specialists in echocardiography and crucially are not designed to replace a full standard transthoracic echocardiogram. Indeed, it is expected that a significant number of patients, in whom a Level 1 echocardiogram is required, will need to have a full echocardiogram performed as soon as is practically possible. This document outlines the minimum dataset for a Level 1 echocardiogram. The accreditation process for Level 1 echo is described separately.